Heat transfer analysis for Casson fluid flow over stretching sheet with Newtonian heating and viscous dissipation effects - Ahmad, Kartini; Wahid, Zaharah; Hanouf, Zahir (2016)
A steady two-dimensional boundary layer flow and heat transfer of a Casson fluid over a stretched plate with Newtonian heating boundary condition is investigated. The governing partial differential equations are first reduced to nonlinear ordinary differential equations by using suit-able similarity transformations before being solved numerically using an implicit finite difference scheme. The features of the flow and heat transfer characteristics for some embedded parameters, such as Casson fluid parameter β, Eckert number Ec, Prandtl number Pr and conjugate Newtonian heating parameter γ, are analyzed and discussed.